Analysis of the Implementation of Metaverse Technology as a Media for Socializing Religious Moderation with a Qualitative Approach At the Palembang Religious Education and Training Center - Angga Madona; Sri Rahayu; Yevi Grata Putra; Tata Sutabri (International Journal of Computer Technology and Science, 2025)
This study aims to analyze the implementation of Metaverse technology as a medium for socializing religious moderation at the Palembang Religious Education and Training Center. Using a qualitative approach, this research explores how Metaverse can facilitate the dissemination of religious moderation values and its potential in improving the understanding of balanced, tolerant, and inclusive religious practices among participants. Data was collected through interviews, observations, and document analysis. The research findings show that Metaverse offers a dynamic and immersive platform to deliver training and discussions on religious moderation, allowing participants to interact more deeply with the material presented. However, challenges such as limited access to technology and understanding of the virtual environment were also found. This research highlights the need for further adaptation and support to maximize the effectiveness of this technology in building religious moderation.